Exploiting inter-tissue stress signaling mechanisms to preserve organismal proteostasis during aging - van Oosten-Hawle, Patricija (Frontiers in Physiology, 2023)
Aging results in a decline of cellular proteostasis capacity which culminates in the accumulation of proteotoxic material, causing the onset of age-related maladies and ultimately cell death. Mechanisms that regulate proteostasis such as cellular stress response pathways sense disturbances in the proteome. They are activated to increase the expression of protein quality control components that counteract cellular damage. Utilizing invertebrate model organisms such as Caenorhabditis elegans, it has become increasingly evident that the regulation of proteostasis and the activation of cellular stress responses is not a cell autonomous process. In animals, stress responses are orchestrated by signals coming from other tissues, including the nervous system, the intestine and the germline that have a profound impact on determining the aging process. Genetic pathways discovered in C. elegans that facilitate cell nonautonomous regulation of stress responses are providing an exciting feeding ground for new interventions. In this review I will discuss cell nonautonomous proteostasis mechanisms and their impact on aging as well as ongoing research and clinical trials that can increase organismal proteostasis to lengthen health-and lifespan.